PENGARUH MODAL SOSIAL, MODAL INSANI DAN MOTIVASI BERWIRAUSAHA TERHADAP KEBERHASILAN PENGUSAHA ‘UKM’ DI KECAMATAN BANJARSARI KOTA SURAKARTA - MRIHRAHAYU RUMANINGSIH (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2017)
The purpose of this research were: (1) To examine and measure the partial influence between social capital, human capital, and entrepreneurship motivation to business success on micro small medium business actors in Banjarsari sub district of Surakarta city (2) To know the most dominant factor of influence to the success of the business to small and medium entrepreneurs in Banjarsari sub district of Surakarta city The study was conducted on UKM entrepreneurs in Banjarsari sub district of Surakarta city. The population in this study is all the UKMs in Banjarsari sub district which amounted to 18,916 UKMs. The samples taken as many as 50 UKMs. The sampling technique was done by simple random method.. Methods of data collection using questionnaires with data analysis techniques using logistic regression analysis. The results of the study found that both partially and simultaneously there is a positive and significant influence of social capital, human capital, and entrepreneurial motivation to the success of the business on small and medium entrepreneurs in Banjarsari sub district of Surakarta city. Social capital has the strongest influence among human capital and entrepreneurship motivation. The success of the business in micro small medium enterprises in Banjarsari sub district of Surakarta city can be explained by the variable of social capital, human capital, and entrepreneurship motivation of 65.50%, while the rest 34, 50% explained by the variable outside the model of this study.